INTEGRATION OF TALUM’S ROLL-BOND HEAT EXCHANGER FOR DIFFERENT APPLICATIONS - Ferčec Janko; Habjanič Rajko (Journal of Energy Technology, 2024)
This article presents the integration of heat exchangers made using the roll-bond technology of Talum d.d., Kidričevo, Slovenia, to applications in refrigeration and heating technology. Talum has more than 30 years of tradition in the production of evaporators for cooling technology and heat exchangers for various purposes, such as absorbers and condensers. The heat exchangers produced in Talum are made of aluminium or aluminium alloys and are categorized as flat heat exchangers. Aluminium and aluminium alloys can be completely recycled after they reach the final phase of their life cycle, which is an essential feature in terms of sustainable construction. The roll-bond technology enables the manufacture of heat exchangers with a complex geometry of channels, which enables them to be used for various applications. Enabled through roll-bond technology, all of these features give the roll-bond heat exchanger a very useful and functional value. In this article, we focused only on some implemented and potential applications of heat exchangers made with using the roll-bond technology.